(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The continuing popularity of mixed martial arts (MMA) events has motivated many martial artists to cross train in grappling disciplines. While largely beneficial for the arts as a whole, many practitioners have nevertheless integrated grappling strategies without considering whether or not their applications are simply sportive or appropriate for self-defense tactics. In this article, I will examine some historical perspectives on the role of grappling on the battlefield from published literature and consider the evidence left to us through historical texts and artwork. Based on over 20 years experience in the grappling arts, I will attempt to show that ground fighting and grappling are necessary components of a complete tactical arsenal, while carefully illustrating the difference in street tactics. I will place specific emphasis on the role of defending the takedown in a modern survival scenario, giving particular attention to the approach employed by the Russian art of Systema.